Manifestation and Management of Cancrum Oris - Mani M. Mani; Sam D. Theogaraj (Indian Journal of Plastic Surgery)
Fifty cases of cancrum oris seen during the past nine years are presented. Exan-thematous fevers—measles, chicken-pox and small-pox occur as the predisposing illness in 48%, of this series.